Estratégias políticas de desfazimento de resíduos eletroeletrônicos na Universidade Federal do Ceará - Ponte, Francisco Roberto Queiroz da (2017)
This work is about the politics estrategy of getting rid of Universidade Federal do Ceará eletronic waste. It analyses specificly how this eletronic garbage is got rid of. The purpose is evaluate how it happens. The approach is qualitative and the procedures are: bibliographic review, documental analysis and interviews. The research was done with managers of student centers, colleges, environmental area teachers, property division workers na with the environmental education division. It is discuted how REEE is got rid of and if there is an acompaniment of these properties after it gives the institution up. After that, it was done a comparison with the processo f another institutions by e-mail and telephone. It was possible to see that in USP there is a reuse Center and in UFRS it is beginning the building of a reuse center with the partnership of the state government and Prefeitura Municipal. The lack of information in the academic community seems to be the biggest problem.